Increased risk of Pneumocystis jirovecii colonization in rheumatoid arthritis patients on biologics and Janus kinase inhibitor - Ya-Chun Huang; Nan-Yao Lee; Meng-Yu Weng (Journal of Microbiology, Immunology and Infection)
Background: The prevalence of Pneumocystis jirovecii (PJ) pneumonia among rheumatic patients is rising. PJ colonization serves as a reservoir for transmission and precedes the development of PJ pneumonia. We aim to clarify the association of PJ colonization in patients of rheumatoid arthritis (RA) treated with biologics or Janus kinase inhibitors (JAKi). Methods: A prospective cohort study was performed from March 2021 to July 2022 in the rheumatology outpatient department of National Cheng Kung University Hospital. We obtained oral-wash samples from asymptomatic RA patients treated with biologic disease-modifying antirheumatic drugs (bDMARDs) and JAKi. A real-time quantitative polymerase chain reaction assay focusing on the mitochondrial large subunit ribosomal ribonucleic acid gene of PJ was applied to detect colonization. Results: One hundred and ten RA patients were enrolled. Adjusted odds ratios (ORs) of PJ colonization were 6.40 (95% CI 1.34-30.57, p-value =0.02) in patients receiving bDMARDs or JAKi. Specifically, in patients treated with bDMARDs the adjusted OR was 8.08 (95% CI 1.57-41.51, p-value=0.012), and a trend toward developing PJ colonization was further identified in patients receiving JAKi (adjusted OR: 4.79, 95% CI 0.89-25.91, p=0.069). Among patients treated with bDMARDs or JAKi, medication duration >3 years and age >60 y/o are risk factors for PJ colonization. Conclusion: RA patients on bDMARDs or JAK inhibitors have an approximately 6-fold higher risk of developing P. jirovecii colonization. Patients treated with bDMARDs had an 8-fold higher risk of P. jirovecii colonization. Risk factors of PJ colonization are medication duration >3 years and age > 60 y/o.